FliW and CsrA Govern Flagellin (FliC) Synthesis and Play Pleiotropic Roles in Virulence and Physiology of Clostridioides difficile R20291 - Zhu, Duolong; Wang, Shaohui; Sun, Xingmin (Frontiers in Microbiology, 2021)
Clostridioides difficile flagellin FliC is associated with toxin gene expression, bacterial colonization and virulence, and is also involved in pleiotropic gene regulation during in vivo infection. However, how fliC expression is regulated in C. difficile remains unclear. In Bacillus subtilis, flagellin homeostasis and motility are coregulated by flagellar assembly factor FliW, flagellin Hag (FliC homolog), and CsrA (Carbon storage regulator A), which is referred to as partner-switching mechanism “FliW-CsrA-Hag”. In this study, we characterized FliW and CsrA functions by deleting or overexpressing fliW, csrA, and fliW-csrA in C. difficile R20291. We showed that fliW deletion, csrA overexpression in R20291, and csrA complementation in R20291ΔWA (fliW-csrA codeletion mutant) dramatically decreased FliC production, but not fliC gene transcription. Suppression of fliC translation by csrA overexpression can be relieved mostly when fliW was coexpressed, and no significant difference in FliC production was detected when only fliW was complemented in R20291ΔWA. Further, loss of fliW led to increased biofilm formation, cell adhesion, toxin production, and pathogenicity in a mouse model of C. difficile infection (CDI), while fliW-csrA codeletion decreased toxin production and mortality in vivo. Our data suggest that CsrA negatively modulates fliC expression and FliW indirectly affects fliC expression through inhibition of CsrA post-transcriptional regulation. In light of “FliW-CsrA-Hag” switch coregulation mechanism reported in B. subtilis, our data also suggest that “FliW-CsrA-fliC/FliC” can regulate many facets of C. difficile R20291 pathogenicity. These findings further aid us in understanding the virulence regulation in C. difficile.